''Efecto de la ultrafiltración en los componentes físico-químicos y funcionales del jugo de naranja (Citrus sinensis)''. - Hidalgo Ortiz, Jessica Leonor (2022)
The present investigation had the objective of evaluating the effect of ultrafiltration on the physical, chemical and functional characteristics of orange juice, to obtain clarified juice through the use of a spiral membrane with a pore diameter of 10μm, as an alternative method to process the juice, without the application of thermal processes that affect its thermosensitive components. In the characterization of the orange juice, the following values were obtained: soluble solids 10°Brix, real density 1.052g/ml, pH 3.4, titratable acidity 0.96%, turbidity 312 FAU (Formazin Attenuation Units), total solids 0.12g /ml, viscosity 0.0012 Pa*s, antioxidant capacity by ABTS 157377.46 μg trolox Eq/100ml, by DPPH 62880.65 μg trolox Eq./100ml, total phenol content of 18.58 mg Ac. Gal/100ml and ascorbic acid 42.64 mg/100ml. The factors evaluated for clarification by ultrafiltration were the working pressure (25-35 Bar) and the feeding speed (110-130 Hz), which significantly influenced the following response variables: color, soluble solids, real density, ionic acidity. , titratable acidity, turbidity, total solids, viscosity, antioxidant capacity and ascorbic acid content. By using the Statgraphics Centurión XV_original program, it was determined that the optimal parameters for obtaining the permeate were provided by the T3 treatment (130 Hz feed speed, 25 Bar pressure), by using the 10μm 1812 spiral Trisep membrane. -TM10-31.